Suppression of Inducible Nitric Oxide Synthase Pathway by 7-Deacetylgedunin, a Limonoid from Xylocarpus sp. - Sarigaputi, Chanin; Sangpech, Nuanpan; Palaga, Tanapat; Pudhom, Khanitha (Planta Medica, 2015)
In this study, limonoids isolated from Xylocarpus plants were tested for their in vitro anti-inflammatory effects. The results demonstrated that only 7-deacetylgedunin (1), a gedunin-type limonoid, significantly inhibited lipopolysaccharide- and interferon-γ-stimulated production of nitric oxide in murine macrophage RAW 264.7 cells. The suppression of nitric oxide production by 1 was correlated with the downregulation of mRNA and protein expression of inducible nitric oxide synthase. Mechanistic studies revealed that the transcriptional activity of nuclear factor-κB, IκBα degradation, and the activation of mitogen-activated protein kinases, stimulated with lipopolysaccharide and interferon-γ, were suppressed by 1.
Keywords: gedunin; limonoid; anti-inflammatory effect; nitric oxide; iNOS